Endoscopic Intramural Surgery Part 1: Resectional Therapies - Wadhwa, Vaibhav; Gupta, Kapil; Erim, Tolga (Digestive Disease Interventions, 2018)
Endoscopic resectional therapies for lesions of gastrointestinal tract have progressed rapidly over the past two decades. Advances in minimally invasive endoscopic approaches continue to emerge and evolve, while boundaries of resection techniques continue to be pushed. The concept of third space endoscopy with mucosal flap as a safety valve has emerged arguably as the most innovative technique among these approaches. We review several techniques for intramural endoscopic resection of lesions of the gastrointestinal tract, but to gain a full understanding of why these exist, we must first examine the background from which they emerged.
Keywords: endoscopy; ESD; STER